2021
DOI: 10.1108/wjemsd-11-2020-0150
|View full text |Cite
|
Sign up to set email alerts
|

A systematic literature review of sustainable entrepreneurship with thematic analysis

Abstract: PurposeThis paper reviews the literature available on sustainable entrepreneurship along with the terms used interchangeably (as the context demands) and explores the themes research have undertaken to explain the concept across multidisciplinary avenues. The purpose of this literature review is to determine the direction of research in the field of sustainable entrepreneurship. It also enables the author to find out the relevance with similar terminologies, i.e. green entrepreneurship, ecopreneurship, ecologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 137 publications
2
12
0
Order By: Relevance
“…As a result, the role of entrepreneurship in sustainability cannot be ignored. Ali [16] contributes to this notion, indicating that corporations organize economic and social life and determine ecological systems' capacity. This argument suggests the correlation between social, economic, and environmental aspects in sustainability, often referred to as the triple bottom line.…”
Section: Results: Theoretical Perspectivesmentioning
confidence: 96%
“…As a result, the role of entrepreneurship in sustainability cannot be ignored. Ali [16] contributes to this notion, indicating that corporations organize economic and social life and determine ecological systems' capacity. This argument suggests the correlation between social, economic, and environmental aspects in sustainability, often referred to as the triple bottom line.…”
Section: Results: Theoretical Perspectivesmentioning
confidence: 96%
“…In terms of sustainability in general and of the concepts traditionally associated with it, there are a number of current reviews in the literature [9][10][11][12], to which we may add a study on green human resource management [13]. However, in the case of the specific concept of green jobs, a systematic analysis of the studies published so far in this field could not be identified.…”
Section: Methodsmentioning
confidence: 99%
“…Our literature review is based on peer reviewed articles which appeared in accredited international journals. We exclude study material not subject to the traditional academic peer-review process (Ali, 2021)Our choice was based on two aspects: First, journal articles are considered as authentic knowledge and have the ultimate impact on the distinct disciplines of research (Armstrong and Wilkinson, 2007). Second, this review seeks to be coherent with previous seminal review works in the field of VC financing and entrepreneurship development, which implemented comparable methodologies (Tykvova, 2017).…”
Section: Methodsmentioning
confidence: 99%
“…We examine prior literature in these four research areas, emphasising the research gaps, as well as the key challenges, and drawing insights that can help to advance VC and entrepreneurship research. By doing so, we discover that most of the empirical studies are based on small and unique samples, frequently too idiosyncratic to yield generalised findings (Tykvova, 2017;Ali, 2021).…”
Section: Introductionmentioning
confidence: 99%